Stocking Your GIS Data Library - Jennifer N. Stone (Issues in Science and Technology Librarianship, 1999)
So, now that you've got the machines and the software, where does the data come from? Data discovery and acquisition can be the most time-consuming part of GIS projects, whether hunting down and purchasing already existing data or creating your own. There are also the issues of documentation and metadata to consider before making an acquisition. A clear understanding of your user group is necessary to know what, exactly, to stock your library with. By using a combination of data from local, state, and federal government sources, plus data created locally and produced by vendors, your collection can be rounded out to serve a diverse user base. The University of Washington will be used as an example. The article will also look at some of the collection development literature concerning both traditional and digital formats.